Notices of the claims of the Hudson's Bay Company and the conduct of its adversaries [electronic resource]. - Gale, Samuel, 1783-1865. (Montreal : Printed by William Gray, 1817)
Errata--p. [162]. Cover title. Attributed to Samuel Gale--A bibliography of Canadiana / Toronto Public Library, no. 1117. "The adversaries ." Electronic reproduction. Mode of access: Internet. 44